OP0143 EFFICACY AND SAFETY OF DAZODALIBEP (VIB4920/HZN4920) IN SUBJECTS WITH SJÖGREN’S SYNDROME: A PHASE 2, RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED, PROOF OF CONCEPT STUDY - St, E. W.; Clair; Wang, L.; Alevizos, I.; Rees, W.; Baer, A.; Ng, W. F.; Noaiseh, G.; Baldini, C. (Annals of the rheumatic diseases, 2023)
BackgroundSjögren’s syndrome (SS) is a chronic, systemic autoimmune disease affecting exocrine glands, primarily the salivary and tear glands, with potentially severe manifestations in multiple organs. No approved disease-modifying therapies exist. Dazodalibep (DAZ) is a biologic antagonist of CD40L.ObjectivesThe objective of this study was to evaluate the efficacy and safety of DAZ therapy in adult SS subjects with moderate-to-high systemic disease activity (NCT04129164).MethodsWe conducted a randomized, double-blind, placebo-controlled, crossover study to evaluate DAZ therapy in adult SS subjects with moderate-to-high systemic disease activity, as defined by a EULAR Sjögren’s Syndrome Disease Activity Index (ESSDAI) score ≥ 5. Eligible subjects were randomized 1:1 to receive intravenous DAZ 1500 mg or placebo (PBO) Q2W x 3 doses, then Q4W x 4 additional doses. Starting on Day 169, subjects initially randomized to DAZ received PBO Q4W x 5 doses and subjects randomized to PBO received DAZ Q4W x 5 doses and were then followed for 12 weeks. The primary endpoint was the change from Baseline in ESSDAI at Day 169. Safety assessments included the incidence of adverse (AEs), serious AEs (SAEs), and AEs of special interest (AESIs).ResultsThe 74 randomized subjects all received ≥1 dose of study medication (DAZ, N=36; PBO, N=38). The baseline demographics and disease characteristics were balanced between the two groups. The change from Baseline to Day 169 in ESSDAI score (LS mean ± SE), was -6.3 ± 0.6 in DAZ-treated subjects compared to -4.1 ± 0.6 in the PBO group, a difference of -2.2 (p = 0.0167). Compared to the PBO group, the DAZ group showed positive trends in the EULAR Sjögren’s Syndrome Patient Reported Index score, and Functional Assessment of Chronic Illness Therapy-Fatigue score at Day 169. A post-hoc responder analysis of subjects achieving high levels (5 and 6 points) of improvement on ESSDAI favored DAZ (61.1% and 60.0%) over PBO (35.1% and 34.3%).The reported AEs were generally mild through Day 169 and similar in frequency between treatment groups. The most frequently reported AEs occurring in ≥5% of DAZ-treated subjects and >PBO were COVID-19, diarrhea, dizziness, ligament sprain, upper respiratory tract infection, contusion, device allergy, fatigue, hypertension, and oropharyngeal pain. Two SAEs were reported in a single DAZ-treated subject: this subject was a 59-year-old female who experienced a grade 3 SAE of COVID-19 infection and later died of unknown cause 46 days after last administration of DAZ (12 days after COVID-19 diagnosis). There was a single AESI of herpes zoster in a DAZ-treated subject.ConclusionDAZ is a potential new therapy for the treatment of systemic disease activity in patients with SS. SS subjects with moderate-to-high systemic disease receiving DAZ experienced a statistically significant reduction in disease activity relative to PBO as measured by the improvement in ESSDAI score. Except for a case of severe COVID-19 infection, DAZ therapy in SS subjects appeared to be well tolerated. Larger controlled trials of DAZ therapy for SS are warranted to further explore its safety profile and confirm its clinical efficacy.Table 1.Efficacy and Safety DataPBO N=38DAZ 1500 mg N=36EfficacyΔESSDAI, LS mean (SE) †-4.1 (0.6)-6.3 (0.6)*ΔESSPRI, LS mean (SE) †-1.12 (0.29)-1.80 (0.31)ΔFACIT-Fatigue, LS mean (SE) †5.8 (1.6)8.1 (1.6)AE Summary, n (%)≥1 AE23 (60.5)28 (77.8)≥1 related AE8 (21)10 (27.8)≥1 SAE01 (2.8)≥1 related SAE00≥1 AE leading to discontinuation00≥1 AESI01 (2.8)≥1 Death01 (2.8)Efficacy endpoints as of Day 169; † Analyzed using MMRM; Comparisons vs PBO; *p<0.05; AE summaries based on AEs that occurred through Day 169; AE, adverse event; AESI, adverse event of special interest; ESSDAI, EULAR Sjögren’s Syndrome Disease Activity Index; ESSPRI, EULAR Sjögren’s Syndrome Patient Reported Index; FACIT-Fatigue, Functional Assessment of Chronic Illness Therapy-Fatigue; PBO, placebo; SAE, serious adverse eventFigure 1.AcknowledgementsFunded by Horizon Therapeutics. Medical writing support provided by B Lujan, PhD, an employee of Horizon Therapeutics.Disclosure of InterestsE. William St. Clair Consultant of: Horizon Therapeutics, Bristol Myers Squibb, CSL Behring, Resolve Therapeutics, Sonoma Biotherapeutics. Royalties: UpToDate, Liangwei Wang Shareholder of: Horizon Therapeutics, Employee of: Horizon Therapeutics, Ilias Alevizos Shareholder of: Horizon Therapeutics, Employee of: Horizon Therapeutics, William Rees Shareholder of: Horizon Therapeutics, Employee of: Horizon Therapeutics, Alan Baer Consultant of: Bristol Myers Squibb, Wan Fai Ng Consultant of: Novartis, GlaxoSmithKline, Abbvie, BMS, Sanofi, MedImmune, Janssen and UCB, Ghaith Noaiseh Consultant of: Novartis, Chiara Baldini Consultant of: GSK, and Sanofi.